Women and Radio in Semporna, Sabah – In the Name of Development Communication - Intan Soliha Ibrahim; Assis Kamu; Jurry Foo; Juliana Abdul Wahab (IKAT: The Indonesian Journal of Southeast Asian Studies, 2022)
In the context of radio, the gist of development communication is how the radio is used to aid social development. Although there are studies on radio listenership, research on women's listening habits in Malaysia is inadequate, although women are dominant radio listeners globally. This study examines factors that motivate women's listening to the radio, mainly in Semporna, Sabah. The central question is how radio has become significant among women in Semporna? This research employs a quantitative research approach. A structured questionnaire was used to obtain information from 294 female respondents. A chi-square test, factor analysis, and Kruskal-Wallis test with Bonferroni correction were used to analyse the data. The findings of the chi-square test analysis revealed a significant link between radio listening and possessing a radio set at home (X2 = 33.871, df = 1, p 0.05). The Kruskal-Wallis test with Bonferroni correction was conducted to see whether the agreement score in listening to the radio for entertainment and peace of mind is different according to four factors: age, marital status, level of education and occupation. Thus, radio is no longer the primary medium to get information, except for undocumented people.